2017
DOI: 10.5937/spsunp1701081r
|View full text |Cite
|
Sign up to set email alerts
|

Coupled fixed point theorems in C*-algebra-valued b-metric spaces

Abstract: In this paper, we give some coupled fixed point results in the framework of C * -algebra-valued b-metric spaces and in particular in the setting of C * algebra-valued metric spaces. These results, with shorter proofs, generalize and improve other theorems recently introduced. We have used a method of reducing coupled fixed point results to the respective ones for mappings with one variable in the framework of b-metric spaces. Finally, two examples are given to support our theoretical work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…To see that the fixed point is unique suppose that x = y such that T x = x, T y = y. Then by (1) (Following Zhenhu et all [10]), We get G (a, b, c) and so, T has a unique fixed point.…”
Section: Main Theorem and Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…To see that the fixed point is unique suppose that x = y such that T x = x, T y = y. Then by (1) (Following Zhenhu et all [10]), We get G (a, b, c) and so, T has a unique fixed point.…”
Section: Main Theorem and Resultsmentioning
confidence: 98%
“…A. Zada et al [9] considered graph theory and studied on common fixed points in the C * -valued metric space endowed with the graph G under G-contractive condition. S. Radenovic and his collegues [10] used a method to reducing coupled fixed point results to the respective ones for mappings with one variable in the framework of b-metric spaces. They also demonstrated that each C * -algebra-valued b-metric space is a cone b-metric space over normal cone with normal constant equal to 1.…”
Section: Introductionmentioning
confidence: 99%
“…For more details on other results from C * -algebra-cone metric spaces that is, from C * -algebra-cone b-metric spaces the reader can be see [40][41][42]44].…”
Section: Remarkmentioning
confidence: 99%
“…Afterward, many researcher work on ‫ܥ‬ * -algebra valued metric space and proved different kind of results. (For reference see [2,3,6,16,17]). In the present manuscript, fixed point theorem are proved with the help of E.A.…”
Section: Introductionmentioning
confidence: 99%